PELAKSANAAN PERJANJIAN KEMITRAAN ANTARA PERUSAHAAN PENGANGKUTAN DENGAN KURIR (Studi Kasus Perjanjian Kemitraan N0.230/PM/MAS/III/2022) - Siti Alfiatul Mukaromah; Maryati Bachtiar; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
This study discusses the cooperation agreement between the transportcompany and the courier (case study of the cooperation agreement No.230/PM/MAS/III/2022)”. An agreement is an act whereby one or more personsbind themselves to one or more other persons. Based on Article 1338 of the CivilCode which reads: